المقبولية وأثرها في أداء المعني من كلام الإمام علي عليه السلام مثالا - الشكري، محمد ياسين (المركز الجامعي احمد زبانة بغليزان - مخبر اللغة والتواصل, 2020)
تناول المحدثون دراسة النصوص من وجهتين، الأولى: الترابط الرصفي، وموضوعه نحو الجملة، والثانية: الترابط المفهومي وموضوعه نحو النص، ونحو النص يستدرك ما لا يدركة نحو الجملة من تشخيص المعني وفهمه بوجود المعايير النصية التي حددها بوجراند، والبحث تناول عنصر المقبولية، ومساحه تطبيقه من أبلغ الكلم- كلام الإمام علي عليه السلام- والصحة اللغوية للنص عامل مهم في قبول النص، لأن المتلقي يحكم على النص من سلامة اللغة والتركيب ومراعاة أفق المتلقي، وأن تعاون المتلقي مع المتكلم يعد شرطا للتواصل، وبه يقبل النص.
The speakers updated the study of texts in two ways, the first: the pavement correlation, and its topic towards the sentence, and the second: the conceptual interconnection and its subject towards the text, and towards the text recovers what he does not realize towards the sentence from the diagnosis of the meaning and his understanding of the existence of textual criteria defined by Bogrand, and the research addressed the element of acceptability, and the area of its application from Inform the speech - the words of Imam Ali, peace be upon him - and the linguistic validity of the text is an important factor in accepting the text, because the recipient rules the text from the integrity of the language and the composition and observance of the recipient’s horizon, and that the recipient’s cooperation with the speaker is a condition for communication, and by which the text is accepted.
Keywords: المقبولية -- علم اللغة النصي -- الهاشمي، علي بن أبي طالب، ت. 40 هـ